From the Cover: ROS-Induced Store-Operated Ca(2+) Entry Coupled to PARP-1 Hyperactivation Is Independent of PARG Activity in Necrotic Cell Death - Munoz, Frances M. (Toxicol Sci, 2017)
2,3,5-tris(Glutathion-S-yl)hydroquinone, a potent nephrotoxic and nephrocarcinogenic metabolite of benzene and hydroquinone, generates reactive oxygen species (ROS) causing DNA strand breaks and the subsequent activation of DNA repair enzymes, including poly(ADP-ribose) polymerase (PARP)-1. Under robust oxidative DNA damage, PARP-1 is hyperactivated, resulting in the depletion of NAD(+) and ATP with accompanying elevations in intracellular calcium concentrations (iCa(2+)), and ultimately necrotic cell death. The role of Ca(2+) during PARP-dependent necrotic cell death remains unclear. We therefore sought to determine the relationship between Ca(2+) and PARP-1 during ROS-induced necrotic cell death in human renal proximal tubule epithelial cells (HK-2). Our experiments suggest that store-operated Ca(2+) channel (SOC) entry contributes to the coupling of PARP-1 activation to increases in iCa(2+) during ROS-induced cell death. Poly(ADP-ribose)glycohydrolase (PARG), which catalyzes the degradation of PARs to yield free ADP-ribose (ADPR), is known to activate Ca(2+) channels such as TRPM2. However, siRNA knockdown of PARG did not restore cell viability, indicating that free ADPR is not responsible for SOC activation in HK-2 cells. The data indicate that PARP-1 and iCa(2+) are coupled through activation of SOC mediated Ca(2+) entry in an apparently ADPR-independent fashion; alternative PAR-mediated signaling likely contributes to PARP-dependent necrotic cell death, perhaps via PAR-mediated signaling proteins that regulate iCa(2+) homeostasis.